Patterns of Care and Outcomes of Primary Adenoid Cystic Carcinoma of the Trachea. (January 2022) - Behbahani, Sara; Barinsky, Gregory L.; Wassef, David; Paskhover, Boris; Kaye, Rachel
Objective: Primary tracheal malignancies are relatively rare cancers, representing 0.1% to 0.4% of all malignancies. Adenoid cystic carcinoma (ACC) is the second most common histology of primary tracheal malignancy, after squamous cell carcinoma. This study aims to analyze demographic characteristics and potential influencing factors on survival of tracheal ACC (TACC). Methods: This was a retrospective cohort study utilizing the National Cancer Database (NCDB). The NCDB was queried for all cases of TACC diagnosed from 2004 to 2016 (n = 394). Kaplan-Meier (KM) and Cox proportional-hazards models were used to determine clinicopathological and treatment factors associated with survival outcomes. Results: Median age of diagnosis was 56 (IQR: 44.75-66.00). Females were affected slightly more than males (53.8% vs 46.2%). The most prevalent tumor diameter range was 20 to 39 mm (34.8%) followed by greater than 40 mm in diameter (17.8%). Median overall survival (OS) was 9.72 years with a 5- and 10-year OS of 70% and 47.5%, respectively. Localized disease was not associated with a survival benefit over invasive disease ( P  = .388). The most common intervention was surgery combined with radiation therapy (RT) at 46.2%, followed by surgery alone (16.8%), and standalone RT (8.9%). When adjusting for confounders, surgical resection was independently associated with improved OS (HR 0.461, 95% CI 0.225-0.946). Tumor size greater than 40 mm was independently associated with worse OS (HR 2.808; 95% CI 1.096-7.194). Conclusion: Our data suggests that surgical resection, possibly in conjunction with radiation therapy, is associated with improved survival, and tumor larger than 40 mm are associated with worse survival.